Aprendendo a física do oscilador harmônico utilizando o ambiente 3D VPython - Jesus, Amanda de Oliveira de (2020)
This project aims to suggest a strategy for teaching physics, which can be applied at any time in high school, using an operational 3D interaction environment. In our case, it was applied to the 3rd year class of the Technical Course in Informatics Integrated to High School, from the Federal Institute of Mato Grosso - Campus Barra do Garças. In this sense, the idealization of the work took place through computational animations, developed using the Python language, on the Vpython platform. Where, we explore the following physical concepts: force, acceleration, speed, mechanical energy, potential energy, kinetic energy, damping cases, pendulum, period, frequency, Newton's and Hooke's laws. We use Tics, as an aid tool in the teaching-learning process. Thus, the execution of the proposal started with the application of the pre-test (verification of what the student is aware of), discussion of the themes (review of the concepts that will be addressed in the animations), application of practical class scripts (manipulation codes) and post-test (student evaluation). We realized that we achieved satisfactory results since, we contemplate the connection of the common curricular grid with the specific grid of the computer course, so that the students when manipulating the codes as proposed in the scripts felt motivated and consequently contributed to the acquisition and understanding of the concepts physicists.